MODEL KOEFISIEN BALISTIK SATELIT LEO SEBAGAI FUNGSI CUACA ANTARIKSA - S.L. Manurung; Heri Sutastio (Jurnal Sains Dirgantara, 2006)
The long term 1996-2003, of star or modified ballistic coefficients, B*, of five Low Earth Orbiting satellite, solar flux, F10.7 and geomagnetic planetary index Ap were analyzed to find out the effect of space weather on the ballastic coefficient of space craft. The daily variation and 81 days per moving average of ballistic coefficient and F10.7 were in phase, while both variation and Ap index were often out phase. Eventhough the mechanism of balliastic coefficient generated by space weather is still not known clearly, there is a statistically closed relation between ballistic coefficient and solar flux. The relationship, called model, is a second order polinomial function with different constants. Using before and after 2003 data of both parameter the models were verified. The range errors are less then the ralative error of pradicted ballistic coefficient of Bepposax satellite obtained by NASA/JFC a month before the satellite reentry.